2011
DOI: 10.3844/ajessp.2011.510.514
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Eco friendly Refrigerants Usage in Air-Conditioner

Abstract: Problem statement: There are two types of global warming contributions through refrigeration and air conditioning systems. The first one is the Direct Global Warming Potential (DGWP) due to the emission of refrigerants and their interaction with heat radiation. The second one is the Indirect Global Warming Potential (IDGWP) due to the emission of Carbon Dioxide (CO2) by consuming the energy that is generated through the combustion of fossil fuels. Most of refrigerants used in vapor Compressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…HFC refrigerants such as R-134a has zero ODP but considerable GWP. Presently, the use of refrigerants such as hydrocarbons (HCs), hydro-fluoro-olefin (HFO), R744 (carbon dioxide), and environmentally safe nanorefrigerants can reduce both ozone depletion potential and global warming potential [15]. It has been found that replacing R-134a with R1234yf [16] had similar thermal performance and with better environmental benefits.…”
Section: Vapor Compression Methodsmentioning
confidence: 99%
“…HFC refrigerants such as R-134a has zero ODP but considerable GWP. Presently, the use of refrigerants such as hydrocarbons (HCs), hydro-fluoro-olefin (HFO), R744 (carbon dioxide), and environmentally safe nanorefrigerants can reduce both ozone depletion potential and global warming potential [15]. It has been found that replacing R-134a with R1234yf [16] had similar thermal performance and with better environmental benefits.…”
Section: Vapor Compression Methodsmentioning
confidence: 99%
“…Patil (2012) reported on the performance of an HFC-404A refrigeration system for a smooth U-tube con-denser and a micro-fin U-tube condenser for various operating conditions and observed that the cooling capacity of the system is increased by 10% and the coefficient of performance of the system is improved up to 17% using a micro-fin tube condenser. Chinnaraj et al (2011) conducted experimental studies on smaller capacity R22 window air conditioner with Electronic Expansion Valve (EEV) is retrofitted with R407C and R290 and compared the performance given by R22, the Coefficient of Performance (COP) given by R407C and R290 is improved in the range of 4.8-7.1 and 8.0-12.3% respectively and the Energy Efficiency Ratio (EER) is increased by 4.2-6.9% for R407C and 6.4-10.8% for R290.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of the project is to develop the cooperation between the government sectors and Halon 1301 users in establishing the management policies of Halon 1301 in Thailand. The activities of the project are categorized into 5 parts: Morehouse (1993); McCulloch (1999); Rubenstein (1993); Abramson et al (2006); Takemura (2010) and Chinnaraj et al (2011). In 1992, the NFPA issued "the NFPA 2001: Standard on Clean Agent Fire Extinguishing Systems".…”
Section: Introductionmentioning
confidence: 99%